2022
DOI: 10.11591/ijece.v12i4.pp4217-4227
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease situation analysis and prediction using machine learning: a study on Bangladeshi population

Abstract: During a pandemic, early prognostication of patient infected rates can reduce the death by ensuring treatment facility and proper resource allocation. In recent months, the number of death and infected rates has increased more distinguished than before in Bangladesh. The country is struggling to provide moderate medical treatment to many patients. This study distinguishes machine learning models and creates a prediction system to anticipate the infected and death rate for the coming days. Equipping a dataset w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Here a third party is needed to measure the blood glucose level and give the patient some sugar [2]. In recent years, machine learning and IoT-based technologies have shown promising results in health [3]- [5], agriculture [6], [7], and other sectors [8] in making automated decisions and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Here a third party is needed to measure the blood glucose level and give the patient some sugar [2]. In recent years, machine learning and IoT-based technologies have shown promising results in health [3]- [5], agriculture [6], [7], and other sectors [8] in making automated decisions and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The SVR is a well-known and influential supervised machine learning technique from a support vector machine (SVM) that finds the best-fitted line for linear and non-linear regressions in predicting COVID-19-related cases [18] . A study of COVID-19 in Bangladesh showed an excellent regression value of 0.8230 and 0.8322 for infected and death cases, respectively, using the radial basis function (RBF) kernel of SVR [19] . Also, a study of COVID-19 on the Turkish population showed that the SVR performed an excellent regression value at 94% with a low root mean square error (RMSE 0.034) and mean absolute error (MAE 0.036) compared to linear regression (LR), bagged tree (BT) and fine tree (FT) algorithms [20] .…”
Section: Introductionmentioning
confidence: 99%